2004
DOI: 10.1889/1.1821377
|View full text |Cite
|
Sign up to set email alerts
|

62.1: Mechanical Reliability of LCD Panels under Static Loading

Abstract: Previous studies of LCD glass strength have demonstrated that it is independent of glass thickness. Instead, it depends primarily on surface defects introduced in the glass during handling, processing and assembling of the LCD panel. This paper focuses on mechanical reliability of such a panel when mounted in the LCD module and subjected to static loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…In the previous study, the value that was obtained when the 0.7-and 1.1-mmthick and 50 × 50-mm Code 1737 AMLCD glass substrates (alkaline-earth boroaluminosilicate glass) were measured was 65.3 ± 0.4 MPa·mm 0.5 [4]. In particular, the corresponding results demonstrated that the mirror constant of glass does not change even if the glass thickness is different.…”
Section: Mirror Radius and Mirror Constantmentioning
confidence: 88%
“…In the previous study, the value that was obtained when the 0.7-and 1.1-mmthick and 50 × 50-mm Code 1737 AMLCD glass substrates (alkaline-earth boroaluminosilicate glass) were measured was 65.3 ± 0.4 MPa·mm 0.5 [4]. In particular, the corresponding results demonstrated that the mirror constant of glass does not change even if the glass thickness is different.…”
Section: Mirror Radius and Mirror Constantmentioning
confidence: 88%
“…The mechanical integrity of LCD glass substrate has been evaluated previously using both the ring-on-ring test for surface strength and vertical bend test for edge strength [1][2][3][4]. Similarly, the mechanical integrity of LCD panel has been evaluated recently using static and dynamic loading in the center region [ 5,6 ]. All of these tests, however, stress a finite region (less than 1 %) of either the substrate or the panel thereby limiting our understanding of total integrity of the whole panel.…”
Section: Theory Of Cylindrical Bendingmentioning
confidence: 99%
“…A companion paper [1] discusses static, or quasi-static loading of LCD modules as well as standard strength testing of stand-alone LCD glass specimens. It is observed that glass thickness has little effect on the strength and that the # 4 1 to propose a standard set-up for impact and static loading of LCD modules…”
Section: Objectives and Backgroundmentioning
confidence: 99%